Makna Teologis Ajaran Rasul Paulus Tentang Karunia Bernubuat Menurut Surat 1 Korintus 14:1-40 - Sugiono, S. (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2020)
The purpose of this study is to find out the results of biblical interpretation of Paul's teachings about the gift of prophecy contained in 1 Corinthians 14: 1-40. The writer in this research uses descriptive qualitative research methods and literature study. The object of this study is the biblical perspective on Paul's teachings on the concept of the gift of prophecy according to 1 Corinthians chapter 14. The form of approach used is the exegesis approach in which data collection techniques are interpreting the text with the help of hermeneutic science studies and assisted by books and literature relating to the context of the gift of prophecy in 1 Corinthians. There are several findings of the principles of truth contained in the discussion as theological implications for the Corinthian church or church at that time.  First, the Gift of Prophecy Is a Gift of the Holy Spirit, 1 Corinthians 12: 1-14: 40, The Apostle Paul writes about the gifts of the Holy Spirit that God bestows to believers (the body of Christ). In Christianity, spiritual gifts (or charismata) are gifts given by the Holy Spirit. Second, the Gift of Prophecy Is the First Gift, In 1 Corinthians chapter 14 Paul also explains the ultimate gift. Paul's thought is not based on the understanding that he is ordering the gifts of the Spirit. Paul had stated earlier in chapter 12 that all gifts are important and are from the same Spirit and aim to build the body of Christ (1 Cor 12: 7). Third, the Gift of Prophecy Serves to Build, Entertain and Advise. The gifts of the Spirit are given by the Holy Spirit with a specific purpose, and that purpose is given by God to believers with the intention of building up the body of Christ or His church, not for personal / commercial / profit interests.